Differential Diet and pH Effects on Ruminal Microbiota, Fermentation Pattern and Fatty Acid Hydrogenation in RUSITEC Continuous Cultures - Julio Ernesto Vargas; Lorena López-Ferreras; Sonia Andrés; Iván Mateos; Egon Henrique Horst; Secundino López (Fermentation, 2023)
The aim of this study was to distinguish effects due to diet composition from those triggered by ruminal pH on fermentation patterns and microbial profiles in a continuous culture system (RUSITEC). The study followed a 2 × 2 factorial design, with two diets varying in the proportions of forage and concentrate and two pH levels in the culture medium. RUSITEC fermenters were used to simulate rumen fermentation and feed digestibility, fermentation end-products, microbial protein synthesis, microbial community, and long-chain fatty acid profiles in the digesta were determined. Multivariate analyses were applied to summarize the overall results. High concentrate (34% cereal grain, 32% hay) diets were more digestible (p < 0.05) than high forage (10% cereal grain, 78% hay) diets, resulting in a greater (p < 0.05) formation of most fermentation end-products and microbial protein in the rumen. However, there were no significant (p > 0.05) differences between diets in methane production. Ciliate protozoa, anaerobic fungi, some fibrolytic bacteria, hydrogenation of oleic acid, and relative proportion of conjugated linoleic acid were increased (p < 0.05) with high forage diets. A decline in rumen pH from 6.8 to 6.4 decreased (p < 0.05) feed digestibility, protein degradability, and the daily outputs of some fermentation end-products (gas, VFA, acetate, ammonia) but had no effect (p > 0.05) on the synthesis of microbial protein, and on the output of methane, propionate, butyrate or lactate. Minor changes in microbial community profile or the fatty acid relative proportions were observed within this pH range. The overall multivariate analysis revealed a clear discrimination between high-concentrate and high-forage diets, with subtler and less-defined pH effects on ruminal fermentation and microbial communities.